2004
DOI: 10.1507/endocrj.51.89
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Hyperplasia Associated with ACTH-dependent Cushing's Syndrome: Comparison of the Size of Adrenal Glands with Clinical and Endocrinological Data

Abstract: Abstract. Diffuse or nodular hyperplasia of adrenal glands is associated frequently with ACTH-dependent Cushing's syndrome. We carried out a retrospective analysis of 28 patients with ACTH-dependent Cushing's syndrome admitted to our institution between 1984 and 1999 in order to clarify the incidence of adrenal hyperplasia in ACTH-dependent Cushing's syndrome and also to determine the correlation between adrenal gland images and clinical, biochemical and endocrinological data. Of the 28 patients, 16 (57%) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Patients with ACTH-dependent Cushing syndrome or Conn's syndrome can manifest as macronodular adrenal hyperplasia [11][12][13][14]. However, no radiological study has reported whether these lesions can show as low an attenuation as lipid-rich adenomas on unenhanced CT.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ACTH-dependent Cushing syndrome or Conn's syndrome can manifest as macronodular adrenal hyperplasia [11][12][13][14]. However, no radiological study has reported whether these lesions can show as low an attenuation as lipid-rich adenomas on unenhanced CT.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that ACTH can induce increased proliferation, particularly under stress conditions (Lotfi & Armelin 1998, Pignatelli et al 2002. Notably, adrenocortical hyperplasia can occur after prolonged ACTH exposure in patients suffering from pituitary tumours producing ACTH, a situation known as Cushing's disease (CD; McNicol 2000, Imaki et al 2004). However, it must not be ruled out that other POMC-derived peptides could be responsible for such effects on adrenocortical hyperplasia (Bicknell et al 2001, Fassnacht et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…during sport training or competition [5]. Urinary free F (UF) excretion has been shown to be a reliable single index of adrenal/cortical secretion and has been accepted as a measurement of the free fraction in plasma [6,7]. Recently, the 24-h urinary F/E ratio has been proposed as a useful indicator for monitoring the overreaching state in elite swimmers [8].…”
Section: Introductionmentioning
confidence: 99%